Lecture de Sébastien Farré, La Suisse et l’Espagne de Franco. De la guerre civile à la mort du dictateur (1936-1975) - Rose Duroux (Cahiers de Civilisation Espagnole Contemporaine)
This book presents the relations betwen the Swiss authorities and the government of general Franco in their different aspects (economic, social, cultural, political). The study covers from July 18th, 1936, beginning of the civil war, to November 27 th, 1975, day of the enthronement of king Juan Carlos. An important place is reserved for economic relations between both countries, which was obvious for a country such as Switzerland whose international role is notably determined by the economic and financial potency of its firms in worldwide economy. Knowing the ideological dimension of the civil war as well as the existence of a public debate in the Swiss society about the Spanish regime, it was essential to grasp the representation of the Other: how the Spanish and the Swiss are perceived respectively; what is the Swiss position but also the evolution of public opinion regarding general Franco. The question of exile during the civil war and world war II is also tackled, as the important migratory movement in the sixties.